Physical Activity, Screen-Based Sedentary Behavior and Physical Fitness in Chinese Adolescents: A Cross-Sectional Study - Dong, Xiaosheng; Ding, Lijie; Zhang, Rui; Ding, Meng; Wang, Baozhen; Yi, Xiangren (Frontiers in Pediatrics, 2021)
Purpose: The aim of this study is to explore the relationship between screen-based sedentary behavior, physical activity and physical fitness among Chinese adolescents. Methods: This study randomly selected adolescents from 10 administrative districts in Shandong, China. The data gathering tools for demographic and other characteristics (gender, age, body mass index and socioeconomic status), PA (PAQ-A) and screen-based sedentary behavior (YRBSS) and physical fitness (NSPFH 2014) were utilized in this study. Statistical analysis was performed by T-test, chi-square test and multiple linear regression. Results: 10,002 adolescents (14.39 years ± 1.79) participated in the study. The results demonstrated that BMI and high TV viewing time had a significant negative correlation with physical fitness, but there was no association between the amount of time spent playing computer/video games and physical fitness among adolescents. High SES and physical activity in leisure time five or more times per week were significantly associated with most dimensions of physical fitness. Conclusions: the results suggest that we not only need to focus on adolescent risk behavior associated with low socioeconomic status and obesity, but also enforce physical activity and reduce sedentary television-watching behavior, which will be crucial pathways and strategies to improve the physical fitness of Chinese adolescents.